ANALISIS PEMAHAMAN DAN KERANGKA BERPIKIR SISWA BERDASARKAN TEORI APOS PADA KELOMPOK SISWA DENGAN TINGKAT SELF-CONFIDENCE BERBEDA - Aulia Khairunnisa, - (2023)
This study aims to analyze and describe students' understanding and frameworks based on the APOS theory in groups of students with different levels of self-confidence in the matter of number patterns at the junior high school level. The method used in this research is qualitative. This research was conducted in class IX at one of the junior high schools in the city of Bandung, West Java. Analysis of students' understanding and thinking framework of APOS based on self-confidence identified that there were students who had high, medium and low levels of self-confidence. Based on this, this research has identified that students who have high self-confidence have a high level of understanding and can complete mathematical comprehension test questions up to the schematic stage, in general students who have moderate self-confidence have a moderate level of understanding and can complete comprehension test questions. mathematics to the object stage, while students who have low self-confidence have a low level of understanding and can solve mathematical comprehension test questions up to the process stage.